Optimising the use of IV zoledronic acid treatment in neck of femur fracture patients: a quality improvement project - Sean Von Hagt; Uma Sirisha Pusapati (Clinical Medicine)
Background: Osteoporosis, defined by reduced bone mass and poor bone quality, leads to a heightened risk of fractures through decreased bone strength and density. Individuals with fragility neck of femur (NOF) fractures, fractures caused through low-trauma injuries, are administered intravenous (IV) zoledronic acid, a bisphosphonate. This quality improvement project (QIP) investigated treatment delays with zoledronic acid and proposes interventions to optimise care for NOF fracture patients. Methods: The QIP was conducted at St Richard’s Hospital, Chichester, with data from 116 patients admitted with NOF fractures between 1 October 2024 and 31 December 2024. The study cohort consisted of 63 patients after deceased patients, peri-prosthetic fractures, and patients’ receiving alternate bone protection or no bone protection had been removed. Data included the day of admission, delays in vitamin D loading and intravenous (IV) zoledronic acid, from prescription to administration, and discharge timelines. Statistical analysis investigated correlations between admission and treatment delays, while contributing factors, such as weekend protocols, procedural inefficiencies and resource availability, were explored. Results: The mean delay from admission to vitamin D being prescribed was 3.03 days, while the actual administration started within 3.77 days (Fig 1).• Zoledronic acid was started at 9.46 days on average. The delay between initiation of zoledronic acid and discharge (9.98 days) suggests that this treatment is a significant factor in determining length of stay.• Thursday admissions showed the greatest delays for both vitamin D loading (4.25 days) and zoledronic acid administration (13.25 days), while Friday and Sunday admissions were the most efficient (Fig 1).• The mean time from patient admission to discharge was 19.80 days.• Others notable delaying factors include obtaining calcium levels before zoledronic acid prescription, postoperative complications (eg, infections or acute kidney injury) and administrative hurdles, such as medication unavailability and lack of formal consent. Insufficient awareness among clinicians regarding fragility fractures and bisphosphonate protocols (BPP) may have also contributed to delays and lack of prescriptions. Conclusion: The findings highlight the impacts of procedural inefficiencies and practices on treatment delays, notably seen on Thursday admissions. Strategies to address these include clinician education on BPP, improving coordination between clinicians and pharmacists, and focused interventions, such as early vitamin D loading protocols and guidelines. Earlier vitamin D loading would allow sooner IV zoledronic acid administration, potentially reducing overall admission lengths and improving patient outcomes. The overall hospitalisation period suggests that zoledronic acid treatment might be a key determinant of discharge timing. Addressing delays in its administration could reduce hospital stay duration.Future plans include evaluating the impact of these interventions through closing the quality improvement loop with a second QIP cycle. This project highlights the importance of timely and coordinated care in enhancing outcomes for NOF fracture patients and offers actionable recommendations to address noted delays.